Analysis of Changes in Desirable Dietary Pattern (DDP) Scores on the Nutritional Status of Toddlers in Island of Borneo - Gabriella Christa Intan Pratiwi; Rudiansyah Rudiansyah; Togu Raja Sitanggang; Ikeu Tanziha (Universitas Teuku Umar, 2025)
The Dietary Diversity Score (DDS) is an important indicator for assessing the quality of food consumption within a population, directly linked to the nutritional status of individuals, particularly toddlers, who are highly vulnerable to nutritional issues. This study aims to analyze changes in DDS scores and their influence on toddler nutritional status, life expectancy, poverty levels, and the Food Security Index (IKP) in Island of Borneo. This research is an observational analytic study with a cross-sectional design. The population in this study consists of 55 cities/districts on the Island of Borneo. The data used are secondary data from 2022 and 2023, analyzed using a simple linear regression test.The results indicate that DDS scores and toddler nutritional status (stunting, wasting, underweight, and overweight) in Island of Borneo show no statistically significant relationships, with p-values of 0.948, 0.288, 0.326, and 0.850 (p > 0.05), respectively. However, there is a significant influence of DDS scores on poverty levels (p = 0.011).